ANALYSIS OF FACTORS RELATED TO INCREASED URIC ACID LEVELS INPATIENTS AT GENTENG GENERAL HOSPITAL, BANYUWANGI - Prabowo, Eko; Lia Suwardani (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
One of the lifestyle diseases caused is degenerative disease. The incidence of degenerative diseases is often related to age and changes in a person's lifestyle. Age is a factor that is directly related to Body Mass Index (BMI). The aim of this study was to determine the factors associated with increased uric acid levels in inpatients at Genteng Hospital, Banyuwangi Regency. This research used an analytical observational design. The sample in this study were inpatients at Genteng Hospital, Banyuwangi Regency, namely 40 respondents. The sampling technique uses purposive sampling. Tools for the data collection process were questionnaires and observation sheets, then analyzed using the Che Square statistical test with α < 0.05. It is known from the research results that from statistical analysis using the che square test it is known that there is a relationship between the factors age, obesity/BMI and family support with increasing uric acid levels in inpatients at Genteng Hospital, Banyuwangi Regency with p value <0.05. For this reason, it is necessary to maintain your diet, to avoid foods that are fatty and have high purine levels. Supported by regular exercise so that blood circulation becomes smooth, thereby preventing the accumulation of fat and high purines in the blood which cause obesity and gout.